The influence of permafrost processes and paludification on landscapes in mountain settings of the Upper Kolyma basin (Western Beringia). (10th April 2022) - Lozhkin, Anatoly; Anderson, Patricia
Abstract: Lithological and paleovegetation data from sites in the Elikchan region of the Upper Kolyma basin provide insights into the permafrost history of the mountain valleys of interior Western Beringia. The Elikchan records show a period of peat accumulation between ∼12, 000 and 9500 cal BP, which parallels trends in the northern coastal lowlands. This interval corresponds to a time when summers were warmer and drier than present and the previously established Betula-Alnus shrub tundra was replaced by Larix-Betula-Populus forest in both the interior valleys and northern lowlands. The Elikchan sites indicate that thermokarst processes continued throughout the Middle and Late Holocene, with the development of small ponds in the middle of ice-wedge polygons, their subsequent expansion to form thermokarst lakes, the periodic drainage or migration of these lakes, and the intermittent formation of stable surfaces as indicated by soil development. The arrival of Pinus pumila in the region ∼10, 000 cal BP suggests an increase in snow cover, a change that would enhance ground insulation, deepen the active layer, and increase permafrost thaw. Although such conditions might favor another interval of peat growth, peat accumulation apparently occurred only during the Early Holocene in the Elikchan region. Modern permafrost-vegetation-climate studies and sensitivity experiments using a Beringian paleoclimate model underscore the importance of seasonality when trying to unravel the complex climate and vegetation feedbacks that have influenced and will continue to affect permafrost landscapes.